The horsewoman : a novel - Patterson, James, 1947-; Lupica, Mike (Little, Brown, and Company, 2022)
Maggie Atwood and Becky McCabe, mother and daughter, both champion riders, vowed to never, ever, go up against one another. Until the tense, harrowing competitions leading to the Paris Olympics. Mother and daughter share a dream: to be the best horsewoman in the world.